Practice makes better? The influence of increased practice on task conflict in the Stroop task. - Najenson, Jonathan; Zaks-Ohayon, Rut; Tzelgov, Joseph; Fresco, Nir (Memory & Cognition, 2025)
The Stroop task is widely used to study attentional control and cognitive flexibility. However, questions about its sensitivity to training and the impact of task conflict on attentional control remain open. We investigated the effects of practice and task conflict on attentional control in the Stroop task, with participants completing four sessions of a Stroop task over 3 weeks in low and high task-conflict conditions. Our results show that the level of task conflict had an impact only in the first session, even though participants remained sensitive to task conflict throughout all four sessions. Moreover, we found that practice reduced response times in the Stroop task, for both congruent and incongruent trials. Nevertheless, the interference between congruent and incongruent stimuli remained consistent over the 3-week period, indicating that inter-condition interference is not affected by training. Our study, therefore, suggests that the extent to which the level of task conflict modulates Stroop task performance is only partially sensitive to training. These findings provide further insights into the role of task conflict and practice in attentional control and cognitive flexibility.